APLIKASI SISTEM INFORMASI GEOGRAFI UNTUK PEMETAAN RUTE DISTRIBUSI LOGISTIK BAGI PENGUNGSI ERUPSI GUNUNG MERAPI MENGGUNAKAN ANALISIS JARINGAN (NETWORK ANALYST) DI KABUPATEN SLEMAN - , ERMA YUNITA, Slamet Hardjo, S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mount Merapi volcano is one that shows the most active volcanism phenomena in the world. Merapi eruptions occur statistically every 2 to 7 years. Since the year 1768 events of merapi eruption recorded more than 80 times the eruption until now. The disaster caused by the volcano is a serious disorders against keberfungsian of a society who are in the immediate surroundings. Attempts in the eruption of Merapi disaster mitigation is necessary especially in terms of providing logistical support to the refugees so that required a manufacturing logistics distribution route for the eruption of Mount Merapi refugees. Research on Logistics Distribution Route Mapping is done in Sleman Regency. This research has the purpose of which is to: (1) charting the refugee barracks located in Sleman, Yogyakarta special region (2) know the accessibility of warehouse logistics towards the location of the eruption of Mount Merapi evacuation barracks (3) make alternate travel route map distribution logistics in Sleman, Yogyakarta special region. There are three methods used in this research are methods of interpretation of imagery, field survey and Network Analyst. Image interpretation method that performs assessment against each of the determinants of the speed of vehicles that is the width of the road and the road conditions. Field Survey on the research is to get points the location of refugee barracks and warehouse logistics points that cannot be directly derived from MapSource. Network Analyst in this research is a method to determine the fastest travel route and a short time to get to the refugee barracks. Research results in the form of existence of Logistics Distribution Route Analysis Maps 1, 2 and 3 in Sleman, scale 1: 250,000 for each warehouse logistics which can include refugee barracks locations within walking distance that has been specified that is 20 kilometres away.